Influence of Digester Temperature on Methane Yield of Organic Fraction of Municipal Solid Waste (OFMSW) - Sailer, Gregor; Silberhorn, Martin; Eichermüller, Johanna; Poetsch, Jens; Pelz, Stefan; Oechsner, Hans; Müller, Joachim (Applied sciences, 2021)
This study evaluates the anaerobic digestion (AD) of the organic fraction of municipal solid waste (OFMSW) and digested sewage sludge (DSS) at lowered temperatures. AD batch tests for CH4 yield determination were carried out with DSS as inoculum between 23 and 40 °C. All results were related to organic dry matter and calculated for standard conditions (1013 hPa, 0 °C). The AD experiments at 40 °C and at 35 °C delivered specific CH4 yields of 325 ± 6 mL/g and 268 ± 27 mL/g for OFMSW alone. At lower temperatures, specific CH4 yields of 364 ± 25 mL/g (25 °C) and 172 ± 21 mL/g (23 °C) were reached. AD at 25 °C could be beneficial regarding energy input (heating costs) and energy output (CH4 yield). Plant operators could increase AD efficiencies by avoiding heating costs. The co-digestion of OFMSW together with DSS could lead to further synergies such as better exploitation of the energy potentials of DSS, but the digestate utilization could become problematic due to hygienic requirements. Efficiency potentials through lowered operating temperatures are limited. In further research, lowered process temperatures could be applied in the AD of energy crops due to large numbers of existing plants.